Influence of Farmer's Characteristics and Managerial Capacities on Rice Farmer's Welfare - Rini Sulistiawati; Novira Kusrini; Imelda Imelda (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2021)
Kubu Raya is one of the largest rice-producing regency in West Kalimantan. However, unfortunately, the success of rice farmers in the area is not followed by an increase in the welfare of farmers because the strategy of increasing income is one of the indicators of welfare that is not used appropriately. This research aims to determine the influence of farmer's characteristics and managerial capacities on the rice farmer's welfare in Kubu Raya Regency. The research is in Kubu Raya Regency, considering that this location is one of the rice farming development regions in West Kalimantan. The data source contains primary and secondary data. The variables of research contain farmer's characteristics, managerial capacities, and farmer's welfare. The data analysis uses SEM (Structural Equation Model) analysis. The result of research indicates that the farmer's characteristics do not influence the farmer's welfare, while the managerial capacities influence the farmer's welfare. It means that farmers need to increase the cultivation technique ability, the management ability, the ability to improve the business, and the ability to adapt to increase their welfare